Impact of smoking on lung cancer treatment effectiveness: a review. (September 2016) - Condoluci, Adalgisa; Mazzara, Calogero; Zoccoli, Alice; Pezzuto, Aldo; Tonini, Giuseppe
Tobacco smoke contains more than 4000 detectable substances, such as polycyclic aromatic hydrocarbons, nicotine, carbon monoxide and heavy metals, which are considered powerful enzymatic inducers that have notable influence on the efficacy and tolerability of many medications through complex pharmacokinetic and pharmacodynamic interactions. As a result, adjustments of drug dosages are required in smokers, both if they continue to smoke or if they quit after smoking cessation treatment. The purpose of this review is to examine the main drug interactions with tobacco smoke clinically relevant, with a closer look on patients developing oncologic diseases.